The Effect of Experience, Independence, and Gender on Auditor Professional Scepticism with Professional Ethics as Moderating - Ratna, Tuti Dewi; Anisykurlillah, Indah (Accounting Analysis Journal, 2020)
This study is aimed to analyze some factors that affect the scepticism of professional auditor. These factors are experience, independence, gender, and professional ethics. Population of this research were 347 auditors who work at the public accounting firm in Central Java and Yogyakarta. Sampling technique used convenience sampling and obtained sample of 83 auditors. For collecting data, the writer used questionnaires. The method of analyzing data was descriptive analysis and multiple regression analysis with IBM SPSS version 21 application. The statistical method used to examine the hypothesis was Moderated Regression Analysis (MRA). The results of this study indicate that the experience of auditors, gender, and professional ethics have a significant effect on auditor professional scepticism. While independence, interaction of experience and professional ethics, interaction of independence and professional ethics, as well as the interaction of gender and professional ethics have no significant effect on professional scepticism of auditors. The conclusion of this study is the need for experience, independence, and high ethical awareness for male and female auditors to remain sceptical in every audit practice.